Arbuscular mycorrhizal fungi mitigate earthworm-induced N2O emissions without significantly reducing total nitrogen leaching losses in a subtropical soil - Ziyi Qian; Xinxing He; Qin Zhong; Tao Liu; Shiqin Yu; Zhongcheng Wang; Yuanhu Shao; Shenglei Fu; Weixin Zhang (Soil Ecology Letters, 2026)

Multifunctional dipole molecules-stabilized buried interface for high-performance air-processed regular perovskite solar cells with minimized energy losses - Kun Luo; Lu Deng; Ziyuan Liu; Xuxia Shai; Meirong Fu; Yue Yu; Xinxing Liu; Xingyu Gao; Dongmei He; Jiajia Zhang; Jiangzhao Chen (Chemical Engineering Journal, 2026)

Divergent filtration mechanisms of fibrous and non-fibrous microplastics in towing-net sampling toward a harmonized framework for abundance correction - Yipu Sui; Xinxing You; Gaobo Guo; Xinle Xu; Liuyi Huang; Chunwei Bi; Shuyue He (Environmental Pollution, 2026)

Numerical investigation of the hydrodynamic characteristics of olive-shaped fishing floats in steady current - Gonghai Lan; Jintao Zhang; Liuyi Huang; Gang Wang; Yuyan Li; Xinxing You; Chunwei Bi; Shuyue He; Jinhui Zhang; Rongjun Zhang; Haoyuan Lv (Ocean Engineering, 2026)

Plant diversity shifts soil phosphorus and nitrogen limitations to carbon processes along latitudinal gradients: Role of nutrient stoichiometry - Belayneh Azene; Wenjie Bao; Chaoying Yang; Awoke Guadie; Yalemzewd Nigussie; Min Cao; Kun Xu; Yun Deng; Hua Huang; Guanghong Cao; Feng Liu; Shangwen Xia; et al. (Forest Ecology and Management, 2026)

Salt and ammonia exposure response and bioaugmentation mechanism in anaerobic digestion of food waste - Qingming He; Yongli Liu; Jie Yang; Xinxing Gao; Wangshui Cai; Xuya Peng; Lei Li (Journal of Environmental Sciences, 2026)

Regulation of air-sea CO2 flux and aragonite saturation state in coral reef ecosystems along the eastern coast of Hainan Island, China - Wei Yang; Zijia Zheng; Peiqiang Zhuang; Jianhang Zhang; Wei Deng; Shengyong Li; Yanmei Liu; Ming He; Yingfeng Chen; Bingbing Yu; Xinxin Xu; Xinxing Li; et al. (Marine Pollution Bulletin, 2026)

Greenhouse gas emissions from black soldier fly composting of silver and silver sulfide nanoparticle-enriched sludge - Jingtao Wu; Lei Xiong; Yuantong Yang; Cui Li; Peng Mao; Qingqiu Zhou; Guangcan Yu; Xingyun Huang; Rajeshwar Dayal Tyagi; XinXing He; Jonathan W.C. Wong (Water Research, 2026)

A fungal polysaccharide from Trametes orientalis: Structural elucidation and multifaceted antitumor mechanisms via metastasis, angiogenesis, and immunomodulation - Wenrui He; Haojing Jiang; Mingming Rong; Xinxing Li; Jing Xu; Yuanqiang Guo (Carbohydrate Polymers, 2025)

Hydrogen bond network suppresses cascade degradation for high-performance air-processed perovskite solar cells - Xinxing Liu; Xiao Han; Yue Yu; Dongmei He; Jianhong Yi; Jiangzhao Chen (Chemical Engineering Journal, 2025)

Simultaneous targeted therapy of multiple top interface defects for high-performance air-processed n-i-p perovskite solar cells - Weitao Chen; Xuxia Shai; Xinxing Liu; Yue Yu; Dongmei He; Chunhua Zeng; Yanlin Song; Jiangzhao Chen (Chemical Engineering Journal, 2025)

Preservation processes of liquid nitrogen spray freezing technology on Sebastes schlegelii in two stages of freezing and frozen storage: Focusing on changes in water status, protein characterization, texture properties and volatile compounds - Weijia Zhang; Zhuyu Yang; Wenjing Zhao; Lianfa Gong; Wentao Liu; He Xu; Lili Sun; Tingwei Zhang; Ya Li; Guiping Wang; Xinxing Xu; Yuanhui Zhao (Food Chemistry, 2025)

Numerical investigations of the micro-sized lunar dust deposition in the human truncated whole lung airways - Lei Jiang; Zhangyu Liu; Hao Jing; Yuan Xue; Bin Wu; Yinghui Li; Honglei Ma; Xinxing He; Jintao Wang; Xinguang Cui (Building and Environment, 2025)

Feeding behavior quantification and recognition for intelligent fish farming application: A review - Yuchen Xiao; Liuyi Huang; Shubin Zhang; Chunwei Bi; Xinxing You; Shuyue He; Jianfeng Guan (Applied Animal Behaviour Science, 2025)

Deep neural network and transfer learning for annual wetland vegetation mapping using sentinel-2 time-series data in the heterogeneous lake floodplain environment - Jinquan Ai; Xinxing Han; Lijuan Chen; Haiqing He; Xiaolong Li; Yongbin Tan; Tianci Xie; Xintao Tang (International Journal of Remote Sensing, 2025)

Minimizing interfacial energy losses via fluorination strategy toward high-performance air-fabricated perovskite solar cells - Xiao Han; Xinxing Liu; Yue Yu; Dongmei He; Jing Feng; Jianhong Yi; Jiangzhao Chen (Chemical Engineering Journal, 2024)

Enhanced therapeutic potential of Flotillins-modified MenSCs by improve the survival, proliferation and migration - Fangfang Cheng; Longkai Ji; Pan Li; Zhisheng Han; Yanan He; Fen Yang; Zhihao Xu; Yonghai Li; Tao Ruan; Xinxing Zhu; Juntang Lin (Molecular Biology Reports, 2024)

Revealing the long-term impacts of plant invasion and reclamation on native saltmarsh vegetation in the Yangtze River estuary using multi-source time series remote sensing data - Jinquan Ai; Lijuan Chen; Haiqing He; Xinxing Han (Ecological Engineering, 2024)

Drag force and filtration performance of square-frame ichthyoplankton sampling net - Gaobo Guo; Xinxing You; Xin Zhuang; Fuxiang Hu; Haopeng Wang; Shuyue He; Liuyi Huang (Ocean Engineering, 2024)

Toxic effect and mRNA mechanism of moon dust simulant induced pulmonary inflammation in rats - Jintao Wang; Yuan Xue; Bin Wu; Ming Lei; Honglei Ma; Xinxing He; Qi Tan; Jian Guan; Wei Song; Renfu Li; Xinguang Cui (Toxicology, 2024)

Interactions between phosvitin and aldehydes affect the release of flavor from Russian sturgeon caviar - Weijia Zhang; Li Liu; Yuanhui Zhao; Tianhong Liu; Fan Bai; Jinlin Wang; He Xu; Ruichang Gao; Xiaoming Jiang; Xinxing Xu (Food Chemistry, 2024)

Correlation investigation between core microbe inoculation and the evolution of flavor characteristics during the storage of sturgeon caviar (Acipenser gueldenstaedtii) - Li Liu; Shixue Lu; Weijia Zhang; Fan Bai; Jinlin Wang; Xuqing Zhang; He Xu; Xiaoming Jiang; Shucai An; Wei Li; Yuanhui Zhao; Xinxing Xu (Food Research International, 2024)

Particle size-dependent and route-specific exposure to liquid crystal monomers in indoor air: Implications for human health risk estimations - Huiju Lin; Xinxing Li; Xian Qin; Yaru Cao; Yuefei Ruan; Michael K.H. Leung; Kenneth M.Y. Leung; Paul K.S. Lam; Yuhe He (Science of The Total Environment, 2024)

Numerical analysis of micro lunar dust deposition in the human nasal airway - Xinguang Cui; Wei Song; Yuan Xue; Hao Jing; Ming Lei; Honglei Ma; Xinxing He; Pengfei Zou; Bin Wu; Jintao Wang (Journal of Hazardous Materials, 2024)

Intercropping with legumes alleviates soil N limitation but aggravates P limitation in a degraded agroecosystem as shown by ecoenzymatic stoichiometry - Haobo Xu; Xiaozhou Huang; Juan Chen; Yazhen Chen; Yingping Wang; Xiaohong Wu; Jun Wang; Hanjie He; Peng Dang; Tao Liu; Xinxing He; Wende Yan (Soil Biology and Biochemistry, 2023)

The g-C3N4 decorated carbon aerogel with integrated solar steam generation and photocatalysis for effective desalination and water purification - He Zhang; Wenmei Luo; Yuping Du; Hao Shi; Guangyong Zeng; Xinxing Yan; Xiaoke Li (Desalination, 2023)

Numerical investigations of the micro lunar dust particles deposition in the human oral respiratory airway - Xinguang Cui; Wei Song; Yuan Xue; Hanxiong Guan; Jinhua Zhang; Xinxing He; Honglei Ma; Ming Lei; Jintao Wang; Yichao Li (Journal of Hazardous Materials, 2023)

Elevation gradient dependence of extreme climate indices on Yunnan Plateau, China - Wenbo Yan; Yunling He; Xinxing Qu (International Journal of Climatology, 2022)
The acceleration of global warming leads to frequent extreme weather events. The sensitivity of high‐elevation regions to global warming makes their extremes more prominent. Based on the software Rclimdex1.0, 15 extreme climate indices from 120 meteorological stations in Yunnan from 1960 to 2019 were calculated. Trend analysis, correlation analysis, and cross‐correlation analysis were used to investigate the spatiotemporal variation characteristics of these extreme climate indices. The results showed that, except CDD, other extreme precipitation indices were negatively correlated with the increase of elevation. The extreme warming indices (SU25, WSDI, TX90p, TN90p) showed an increasing trend with the increase of elevation, while the extreme cold indices (CSDI, FD0, TX10p, TN10p) showed a decreasing trend with the increase of elevation. The rate of nocturnal warming at high elevations is higher than that at low elevations. The change rate of extreme warmth indices (SU25, WSDI, TX90p, TN90p) and extreme cold indices (FD0, CSDI, TX10p, TN10p) was negatively correlated ( p

Assessing the fractionation and bioavailability of heavy metals in soil–rice system and the associated health risk - Yuanyuan Wang; Weiwei Xu; Jizhou Li; Yinxian Song; Ming Hua; Wenbo Li; Yubo Wen; Tianyuan Li; Xinxing He (Environmental Geochemistry and Health, 2022)

Disturbance intensity overwhelms propagule pressure and litter resource in controlling the success of Pontoscolex corethrurus invasion in the tropics - Xinxing He; Shengjie Liu; Jin Wang; Jianming Gan; Zhipeng Li; Tao Liu; Weixin Zhang; Xiaoming Zou; Xiaodong Yang (Biological Invasions, 2020)

The T cell activating properties and antitumour activity of Staphylococcal Enterotoxin-like Q - Yanan He; Yuliang Sun; Yakun Ren; Liang Qiao; Rui Guo; Jiang Du; Xinxing Zhu; Yanli Liu; Juntang Lin (Medical Microbiology and Immunology, 2019)

Two new xanthones from the pericarp of Garcinia mangostana - Xiaojun Zhou; Luan He; Xinxing Wu; Yanxia Zhong; Juan Zhang; Yuanxing Wang; Bin Wang; Zhifang Xu; Shengxiang Qiu (Natural Product Research, 2015)

Geological characteristics and model ages of Marius Hills on the Moon - Jun Huang; Long Xiao; Xinxing He; Le Qiao; Jiannan Zhao; Hui Li (Journal of Earth Science, 2011)